2022
DOI: 10.3389/fcvm.2022.907539
|View full text |Cite
|
Sign up to set email alerts
|

Use of fibrates is not associated with reduced risks of mortality or cardiovascular events among ESRD patients: A national cohort study

Abstract: BackgroundAlthough a recent study reported that fibrates are associated with a low risk of cardiovascular (CV) death and can postpone the need for long-term hemodialysis in patients with advanced chronic kidney disease (CKD), little is known regarding whether the CV protective effects of fibrates extend to patients with end-stage renal disease (ESRD). The present study compared CV outcomes and mortality among patients with ESRD treated with fibrates, statins, neither, or their combination.MethodsThis cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Messow et al’s meta-analysis, which incorporated 13 studies examining statin-treated CKD, revealed an escalation in cardiovascular risk with the progression of CKD stages [ 23 ]. Ho et al’s cohort study found that fibrates may not effectively reduce cardiovascular risk [ 24 ]. This study focused on elucidating the influence of sacubitril/valsartan on lipid metabolism in individuals with CKD and CVD, intending to offer insights for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Messow et al’s meta-analysis, which incorporated 13 studies examining statin-treated CKD, revealed an escalation in cardiovascular risk with the progression of CKD stages [ 23 ]. Ho et al’s cohort study found that fibrates may not effectively reduce cardiovascular risk [ 24 ]. This study focused on elucidating the influence of sacubitril/valsartan on lipid metabolism in individuals with CKD and CVD, intending to offer insights for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the primary reason for withdrawal from the NHI program is death, especially for individuals with catrostrophic illness whose high medical expenditures were nearly fully covered by NHI (Wu et al, 2012). Less common reasons include permanent emigration, being missing for more than 6 months, or being incarcerated for more than 6 months (Chung et al, 2022;Ho et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A population-based study in Taiwan showed that fibrates reduced the risk of cardiovascular events and delayed dialysis initiation [ 11 ]. However, the data are limited and inconsistent in the CKD population [ 12 ]. Fibrate use is poorly studied in the Japanese population, especially in patients with CKD, as its use was limited in the past because of the contraindication for combined use with statins.…”
Section: Introductionmentioning
confidence: 99%